Chemical and bioactive characterization of Impatiens balsamina L. pink flowers and their application in a Portuguese pastry product - Pires Junior, Eleomar de O. (2021)
The rose petals of the species Impatiens balsamina L. were investigated. In this way the nutritional composition, phenolic profile and its bioactive composition were evaluated. Next, the extract obtained was applied to a product of the Portuguese pastry "bombocas". Proving to be a possible promising natural colour for the food industry.